Epigenetic Regulation of Megaspore Mother Cell Formation - Jiang, Ting; Zheng, Binglian (Frontiers in Plant Science, 2022)
In flowering plants, the female gametophyte (FG) initiates from the formation of the megaspore mother cell (MMC). Among a pool of the somatic cells in the ovule primordium, only one hypodermal cell undergoes a transition of cell fate to become the MMC. Subsequently, the MMC undergoes a series of meiosis and mitosis to form the mature FG harboring seven cells with eight nuclei. Although SPL/NZZ, the core transcription factor for MMC formation, was identified several decades ago, which and why only one somatic cell is chosen as the MMC have long remained mysterious. A growing body of evidence reveal that MMC formation is associated with epigenetic regulation at multiple layers, including dynamic distribution of histone variants and histone modifications, small RNAs, and DNA methylation. In this review, we summarize the progress of epigenetic regulation in the MMC formation, emphasizing the roles of chromosome condensation, histone variants, histone methylation, small RNAs, and DNA methylation.